Pelatihan Pengisian Beban Kinerja Dosen (BKD) melalui Aplikasi SISTER di Lingkungan Akademi Keuangan dan Perbankan Nusantara - Adi Ahmad; Syamsul Rizal; Muhammad Jamil; Erni Wiriani; Esti Alemia Puspita (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
The training on filling the Lecturer Performance Load (BKD) through the SISTER Application within the Nusantara Academy of Finance and Banking aims to improve lecturers' understanding and ability to report their academic performance accurately and on time. BKD is an important instrument in assessing lecturer productivity in accordance with the duties and functions of the tridharma of higher education. The SISTER application developed by the Ministry of Education, Culture, Research and Technology (Kemdikbudristek) facilitates online BKD reporting. However, many lecturers face obstacles in operating this application, thus requiring special assistance. Through this training, participants are equipped with practical knowledge about the procedures for filling out BKD in accordance with applicable standards, utilizing features in the application, and solving common problems that are often encountered. The results of this activity are expected to improve the efficiency and quality of lecturer performance reporting, as well as support the assessment process and career development of lecturers in the institution. This training is also a strategic step to improve accountable and information technology-based university governance.